Childhood obesity and Craniofacial growth: recapitulating orthodontic implications - Acharya, Swati S; Mishra, Sumita; Bai, Pavithra M; Mohanty, Pritam (Bangladesh Journal of Orthodontics and Dentofacial Orthopedics, 2016)
Childhood obesity is a significant concern in many countries and is a condition of systemic inflammation to an impaired immunity. It is usually characterized by a low-grade inflammation depending mostly on the release of cytokines, adipokines and reactive oxygen. There is a vast difference of craniofacial morphology in obese and normal adolescents. The visceral adipose tissue (VAT) is the primary source of pro-inflammatory cytokines in obese individuals. This narrativereview article focuses on the profile of immune response and illustrates the craniofacial morphological changes in obese adolescents. Furthermore, interventional studies which were aimed at preventing early occurrence of malocclusion in obese adolescents is elaborated. Ban J Orthod & Dentofac Orthop, April 2016; Vol-6 (1-2), P.13-23